Penerapan Token Ekonomi untuk Meningkatkan Kemandirian Anak Usia 5-6 Tahun di Lembaga PAUD - Anista, Dewi Zhintia Noor; Anwar, Rosyida Nurul; Afifah, Sofia Nur (Jurnal Pendidikan Anak Usia Dini, 2024)
The research objective was to determine the application of economic tokens in increasing children's independence in kindergarten in Kwadungan District. This research was conducted in Kindergartens located in Kwadungan District, including DW Karangsono 1 Kindergarten, DW Karangsono 2 Kindergarten, DW Karangsono 3 Kindergarten, Dharma Wanita Mojomanis Kindergarten, Dharma Wanita Banget Kindergarten, Dharma Wanita Budug Kindergarten with a total sample of 60 students, with 30 students in the experimental class and 30 students in the control class. The research method used in this research is to use observational data collection and documentation to observe the behaviour of research subjects directly. The results of this study are that the initial factor for child independence comes from the parents or the house first. Then, after the child is in school, the teacher as an educator is also tasked with increasing the child's independence. Based on the data processing results through SPSS with the Paired Sample T-Test, the significance value was 0.000 <0.05. Therefore, it can be concluded that Ha is accepted and Ho is rejected. That is, there are differences in economic tokens to increase independence in children aged 5-6 years in the experimental class including Karangsono 1 PKK Kindergarten, Karangsono 2 PKK Kindergarten, Karangsono 3 PKK Kindergarten, and the control class includes Dharma Wanita Mojomanis Kindergarten, Dharma Wanita Banget Kindergarten, Kindergarten Dharma Wanita Budug. This situation proves that children treated with economic tokens experience increased independence.